Immediate effects of training with musical mnemonics on verbal memory in children - Knott, David, author; LaGasse, Blythe, advisor; Knight, Andrew, advisor; Seger, Carol, committee member (Colorado State University. Libraries, 2016)
The purpose of this study was to compare the effects of musical mnemonics versus spoken word in training verbal memory in children. A randomized control trial of typically-developing 9-11 year old children was conducted using the Rey Auditory Verbal Learning Test (RAVLT), a test measuring a participant’s ability to recall a list of 15 words over multiple exposures. Members of the group that listened to words sung to them recalled an average of 20% more words after listening to and recalling an interference list than members of the control group that listened to the same words spoken. This difference persisted, though slightly smaller (17%) when participants recalled words after a 15-minute waiting period. Group participants who listened to words sung demonstrated a higher incidence of words recalled in correct serial order. Potential contributions of musical mnemonics during the learning phase were also considered. While key findings were statistically significant, other examples of improved performance for participants who listened to words sung were below the level of significance. At times large standard deviations and varied performance across tasks may suggest these performance effects are susceptible to individual differences, or that heterogeneity of cognitive functioning levels was represented in the sample. These findings suggest that musical mnemonic training may be more effective than rehearsal with spoken words in verbal memory learning tasks in 9-11 year olds.